2023
DOI: 10.1126/scitranslmed.adg1659
|View full text |Cite
|
Sign up to set email alerts
|

Early-set POMC methylation variability is accompanied by increased risk for obesity and is addressable by MC4R agonist treatment

Abstract: Increasing evidence points toward epigenetic variants as a risk factor for developing obesity. We analyzed DNA methylation of the POMC (pro-opiomelanocortin) gene, which is pivotal for satiety regulation. We identified sex-specific and nongenetically determined POMC hypermethylation associated with a 1.4-fold (confidence interval, 1.03 to 2.04) increased individual risk of developing obesity. To investigate the early embryonic establishment of POMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
4
0
3
Order By: Relevance
“…Setmelanotide was recently granted approval by the U.S. Food and Drug Administration (FDA) 19 Efficacy of Setmelanotide was determined in individuals with rare genetic mutations that disrupt the MC4r pathway such as POMC 36 . Of interest, a recent study found that Setmelanotide can also affect treat individuals with dysregulated methylation in the POMC gene, which further suggests that epigenetic dysregulation of this pathway may be treated with Setmelanotide 37 . A limitation of the current study is that we do not know which specific cell types in the hypothalamus are responsible for the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Setmelanotide was recently granted approval by the U.S. Food and Drug Administration (FDA) 19 Efficacy of Setmelanotide was determined in individuals with rare genetic mutations that disrupt the MC4r pathway such as POMC 36 . Of interest, a recent study found that Setmelanotide can also affect treat individuals with dysregulated methylation in the POMC gene, which further suggests that epigenetic dysregulation of this pathway may be treated with Setmelanotide 37 . A limitation of the current study is that we do not know which specific cell types in the hypothalamus are responsible for the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…What is the potential significance of epigenetics in obesity? Analysis of a large cohort ( n = 1383) found increased DNA methylation in a variably methylated region in the POMC gene, particularly in women 54 . POMC methylation is very stable over time and is present before the onset of obesity.…”
Section: Patient Care and Translationmentioning
confidence: 98%
“…Neben genetischen Varianten sind auch epigenetische Veränderungen am POMC-Gen beschrieben [43,44]. Personen mit einer veränderten DNA-Methylierung am POMC-Gen haben ein 1,4-fach erhöhtes Risiko für die Entwicklung einer Adipositas [44].…”
Section: Mutationen Im Pomc-genunclassified
“…Neben genetischen Varianten sind auch epigenetische Veränderungen am POMC-Gen beschrieben [43,44]. Personen mit einer veränderten DNA-Methylierung am POMC-Gen haben ein 1,4-fach erhöhtes Risiko für die Entwicklung einer Adipositas [44]. Diese differenzielle Methylierung war zudem invers mit der POMC-Expression in den entsprechenden exprimierenden Neuronen assoziiert [44].…”
Section: Mutationen Im Pomc-genunclassified
See 1 more Smart Citation